The association between non-regular work patterns and insomnia among Korean wage workers: the fifth Korean working condition survey - Kim, Ho-Yeon; Choi, Juho; Lim, Hyun-Mook; Park, Chamjin; Hong, Yun-Chul (Annals of occupational and environmental medicine, 2021)
Non-regular workers are steadily increasing on account of improving corporate productivity. They are classified as non-permanent, part-time, or non-typical workers. Non-regular work has a negative impact on workers' physical and mental health. This study analyzed the relationship between non-permanent, part-time and non-typical work and insomnia among Korean wage workers, and investigated the differences and interactions between different work patterns. The Fifth Korean Working Conditions Survey was used in this study. Non-regular work patterns were classified into 7 types: type 1, sole non-permanent; type 2, sole part-time; type 3, sole non-typical; type 4, part-time-non-typical; type 5, non-permanent-non-typical; type 6, non-permanent-part-time; type 7, all inclusive. Insomnia was measured on a scale from "normal sleep" to "insomnia" based on the 3-item Minimal Insomnia Symptom Scale. Multiple logistic regression was used to analyze the association between non-regular work patterns and insomnia among wage workers. After multivariate adjustment, a significantly increased odds ratio (OR) for insomnia was found in types 1, 2, 3, 4, 5, 6, and 7 of non-regular work patterns compared to regular work patterns. After stratification for shift and night work, the OR of the group with shift and night work was higher than that of the group without shift and night work. Insomnia was significantly associated with non-regular work patterns. This association was prominent in workers with shifts and night work. This finding suggests that proper work patterns may be needed to reduce the risk of insomnia among Korean wage workers and workers who initially had insomnia should consider these results before placement.